Implaksi penetapan tarif cukai hasil tembakau terhadap rokok ilegal: pengaruh tarif pita cukai hasil tembakau terhadap rokok ilegal - Warit Aziz; Rr. Herini Siti Aisyah; Radian Salman; Indrawati (Universitas Muhammadiyah Surabaya, 2025)
Excise is state income that is not included in the tax bracket. Excise on tobacco products is part of excisable goods. Determination of excise rates for tobacco products is determined in Law No. 39 of 2007 in addition to further Minister Finance of Regulation 191/PMK.010/2022 governs this. When determining the excise rates tobacco on products, issues arise with respect to things like the steadily rising tax excise rates on tobacco products, the relationship between the vertical excise tax regulations on tobacco products and the effects of the steadily rising tobacco product excise rates on the emergence of illicit cigarettes. The purpose of this study is to investigate issues with tobacco product excise in order to reduce the spread of illicit cigarettes, which cause losses for the state. A conceptual, statutory, and normative legal approach are all combined in the study technique. The Ministry of Finance's examination of its fiscal strategy, which takes into account a number of criteria, is the basis for the causes driving up tax rates on tobacco goods. The legislation governing tobacco product excise tax rates and the guidelines set forth by the minister of finance are irreconcilable. There is no denying that the effects of tobacco product excise taxes contribute to the distribution of illicit cigarettes.